2020
DOI: 10.1111/1751-7915.13636
|View full text |Cite
|
Sign up to set email alerts
|

Elevated intracellular cyclic‐di‐GMP level in Shewanella oneidensis increases expression of c‐type cytochromes

Abstract: Electrochemically active biofilms are capable of exchanging electrons with solid electron acceptors and have many energy and environmental applications such as bioelectricity generation and environmental remediation. The performance of electrochemically active biofilms is usually dependent on c-type cytochromes, while biofilm development is controlled by a signal cascade mediated by the intracellular secondary messenger bis-(3ʹ-5ʹ) cyclic dimeric guanosine monophosphate (c-di-GMP). However, it is unclear wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 69 publications
3
13
0
Order By: Relevance
“…Biofilm formation of the CY3 strain (solely engineering c ‐Cyts) and RF‐CY (co‐engineering of RF and c ‐Cyts) strain on the carbon cloth were substantially thicker than that of the DL0 strain. The results demonstrated that the reinforcement of c ‐Cyts could increase the thickness of biofilm, thereby improving the EET efficiency, which was consistent with previous reports (Jing et al, 2020; Mukherjee et al, 2020; Ng et al, 2020). In summary, the elevated RF production was capable of promoting MET, and the synergistic expression of c ‐Cyts promoted biofilm formation, thereby remarkably enhancing the efficiency of EET.…”
Section: Resultssupporting
confidence: 92%
“…Biofilm formation of the CY3 strain (solely engineering c ‐Cyts) and RF‐CY (co‐engineering of RF and c ‐Cyts) strain on the carbon cloth were substantially thicker than that of the DL0 strain. The results demonstrated that the reinforcement of c ‐Cyts could increase the thickness of biofilm, thereby improving the EET efficiency, which was consistent with previous reports (Jing et al, 2020; Mukherjee et al, 2020; Ng et al, 2020). In summary, the elevated RF production was capable of promoting MET, and the synergistic expression of c ‐Cyts promoted biofilm formation, thereby remarkably enhancing the efficiency of EET.…”
Section: Resultssupporting
confidence: 92%
“…In an analysis of proteins involved in c-di-GMP homeostasis of 42 algae strains, six novel sensory domains have been recently described [18], including a novel CSS domain variant in a c-di-GMP phosphodiesterase presumably involved in sensing the redox state of the periplasm [79]. High c-di-GMP content is associated with higher expression of c-type cytochromes in S. oneidensis MR-1 [80], and represents a primary candidate to mediate RIBF in Shewanella. Other nucleotide secondmessenger pathways, such as cyclic di-GMP-AMP (cGAMP) signaling, may play regulatory roles in distinct bacterial species.…”
Section: Trends In Microbiologymentioning
confidence: 99%
“…A subsequent study has shown that the diguanylate synthase is involved in regulating the global level of cyclic-di-GMP (c-di-GMP) in MR-1 cells and facilitating biofilm formation on electrodes [52]. In addition, another study has also suggested that elevated intracellular c-di-GMP levels in MR-1 increase the expression of c-type cytochromes, thereby correlating the biofilm formation with EET [53]. However, since these studies have been conducted independently using different experimental settings, our knowledge on the formation and functioning of EABFs seems to be fragmentary.…”
Section: Biofilm Formation For Electrochemical Interactions With Elecmentioning
confidence: 99%